2016
DOI: 10.1177/1035304616674613
|View full text |Cite
|
Sign up to set email alerts
|

Is it better to invest in hard or soft skills?

Abstract: Increasing awareness of the productive potential of soft skills has sparked a discussion of their systematic and purposeful development. However, education systems pay only limited attention to this topic in most countries and remain focused on the development of hard skills. Is this approach rational or inadequate? This article provides new evidence on different aspects of the wage returns to soft skills (as an approximation of their productivity), and thereby contributes significantly to the discussion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 16 publications
6
66
1
22
Order By: Relevance
“…These findings are consistent with Fairlie and Holleran (2012), who found that individuals with specific personality traits seem to benefit more from entrepreneurial training programs than people without such characteristics. Our results are also linked with research on the productive potential of soft skills and with the recommendations for balanced development of hard and soft skills (Ruback, 2015;Balcar, 2016).…”
Section: Introductionsupporting
confidence: 53%
“…These findings are consistent with Fairlie and Holleran (2012), who found that individuals with specific personality traits seem to benefit more from entrepreneurial training programs than people without such characteristics. Our results are also linked with research on the productive potential of soft skills and with the recommendations for balanced development of hard and soft skills (Ruback, 2015;Balcar, 2016).…”
Section: Introductionsupporting
confidence: 53%
“…It may be explained by their productivity and transferability across employers who compete for workers with these personal traits. Moreover, gender neutrality of wage returns to non‐cognitive skills corresponds to conclusions by Balcar (), who approximated them by job requirements for 15 soft skills (e.g., communication, cooperation, problem‐solving, leadership, etc. ).…”
Section: Resultsmentioning
confidence: 54%
“…The remuneration of non‐cognitive skills deserves special attention as they are, together with education, the most important wage determinant in the Czech Republic (see Balcar, for empirical evidence). Therefore, it was not surprising that the association with a role of the breadwinner and the performance‐oriented behaviour, such as the need to excel, persistence, diligence (approximated by a difference between the number of hours truly devoted to work and the official workload) and low absence from work were found highly statistically significant (Model 5 in Table ).…”
Section: Resultsmentioning
confidence: 99%
“…E.g. issues of interest are mentoring in the workplace as a part of passing various practices in an employers' organization [6], the efficiency of gaining the entrepreneurial skills the graduates will need to work successfully after the university [7], advantages and disadvantages in the forming of narrow and wide specialized skills of future university graduates and the need for employers to participate in this process [8]. It is noted that training in the workplace arranged by the employer plays a special role in the preparation of graduates.…”
Section: Literature Reviewmentioning
confidence: 99%